Rational design of a NIR fluorescent probe for highly selective sensing of NAD(P)H quinone oxidoreductase 1 in living systems - Yang, Fangyu; Zhu, Li; Yan, Fei; Zhang, Houli; Liang, Guobiao (Frontiers in Chemistry, 2025)
NAD(P)H quinone oxidoreductase 1 (NQO1) plays a critical role in catalyzing the reduction of quinones, thereby exerting both chemical protection and biological activation. The expression level of NQO1 in various tumor cells, especially glioma, lung cancer, colon cancer and breast cancer cells, is higher than that in normal tissues, the detection of NQO1 activity is important to understand tumor development mechanisms. Herein, a near-infrared (NIR) fluorescent probe DDANQ was rationally designed and synthesized through a systematic approach. The optical properties and enzyme selectivity of DDANQ were also elucidated by chemical calculation and molecular docking methods. The results showed that DDANQ showed excellent stability, and displayed good selectivity and sensitivity toward NQO1. DDANQ could be used as a molecular tool to elucidate the activity and function of NQO1 in physiological and pathological processes, which could provide valuable insights for tumor diagnosis and treatment.